ASAS-ASAS DESENTRALISASI PEMERINTAHAN DALAM KITAB BAB AL-QAWA’ID - T. Fahrul Gafar; Amri Hakim; M. Fajar Anugerah; Zamhasari (GoAcademica Research dan Publishing, 2021)
This study aims to explain the principles of decentralization of the government of the Kingdom of Siak Sri Indrapura as one of the major kingdoms in the historical trajectory of the Riau and Indonesian governments which has a Constitution or official law for the administration of state government which is recognized by the Dutch East Indies Government. This study uses a qualitative method with a descriptive type and in the form of library research. In this study, the author attempts to read, understand, analyze, and interpret the book of Bab Al-Qawa'id. With this approach, type, and form of research, it will certainly be able to explain comprehensively about the principles of government decentralization that occurred during the heyday of the Siak Kingdom. The kingdom of Siak Sri Indrapura was founded in 1723 AD. Runs with a reign led by 12 Sultans. The peak of the glory of the Siak Sri Indrapura Kingdom began during the reign of the 11th Sultan, SultanSyarif Hasyim (1889-1908). It was during his reign that the book that prevailed in Siak was born and is a book that contains guidelines for the administration of the Siak Kingdom Government.